Effectiveness of Baby Massage On Motor Development In Babies: Literatur Review - Afrida, Hasya Khairina; Ardiansyah, Jepri (International Journal of Social Research, 2024)
Baby massage is a touch therapy that involves massaging the baby with the aim of helping speed up the baby's motor development process. This research aims to determine the effectiveness of baby massage on baby's motor development. A literature review was conducted using a PICO search in the Google Scholar database. The research results show that massage can be done on babies with a frequency of 1-2 times/day for 1 month and lasts 10 to 15 minutes, providing tactile stimulation before/after bathing with p<0.05 gives good results. has an important influence on motor development, babies who receive massage and movement training have faster growth and development than babies who do not receive massage and movement training. Baby massage is one way of manual therapy that influences soft tissue to improve baby's health